Influence of N-Hexane Inhalation on the Enantioselective Pharmacokinetics and Metabolism of Verapamil in Rats - Mateus, Fabiano H.; Lepera, José Salvador [UNESP]; Marques, Maria Paula; Boralli, Vanessa B.; Lanchote, Vera L. (Wiley-liss, 2010)
Verapamil (VER) is commercialized as a racemic mixture of the (+)-(R)-VER and (-)-(S)-VER enantiomers. VER is biotransformed into norverapamil (NOR) and other metabolites through CYP-dependent pathways. N-hexane is a solvent that can alter the metabolism of CYP-dependent drugs. The present study investigated the influence of n-hexane (nose-only inhalation exposure chamber at concentrations of 88, 176, and 352 mg/m(3)) on the kinetic disposition of the (+)-(R)-VER, (-)-(S)-VER, (R)-NOR and (S)-NOR in rats treated with a single dose of racemic VER (10 mg/kg). VER and NOR enantiomers in rat plasma was analyzed by LC-MS/MS (m/z = 441.3 > 165.5 for the NOR and m/z 455.3 > 165.5 for the VER enantiomers) using a Chiralpak (R) AD column. Pharmacokinetic analysis was performed using a monocompartmental model. The pharmacokinetics of VER was enantioselective in control rats, with higher plasma proportions of the (-)-(S)-VER eutomer (AUC(0-infinity) = 250.8 vs. 120.4 ng/ml/h; P <= 0.05, Wilcoxon test). The (S)-NOR metabolite was also found to accumulate in plasma of control animals, with an S/R AUC(0-infinity) ratio of 1.5. The pharmacokinetic parameters AUC(0-infinity), Cl/F, Vd/F, and t(1/2) obtained for VER and NOR enantiomers were not altered by nose-only exposure to n-hexane at concentrations of 88, 176, or 352 mg/m(3) (P > 0.05, Kruskal-Wallis test). However, the verapamil kinetic disposition was not enantioselective for the animals exposed to n-hexane at concentrations equal to or higher than the TLV-TWA. This finding is relevant considering that the (-)-(S)-VER eutomer is 10-20 times more potent than R-(+)-VER in terms of its chronotropic effect on atrioventricular conduction in rats and humans. Chirality 22:29-34, 2010. (C) 2009 Wiley-Liss, Inc.
Keywords: verapamil; n-hexane; enantiomers; metabolism; rats; pharmacokinetics